Effectiveness of Public Service Announcements in Promoting Social Causes - admin1, admin1 (Social Sciences Journal, 2023)
The study looked at effectiveness of public service Announcement in promoting social causes particularly among Eket residents, and this depends on several factors. PSAs often address a wide range of social issues, including public health, environment conservation, social justice, human rights, etc. PSAs typically leverage the persuasive power of mass media channels including television, radio, print and digital platforms. The messages sent across most times act as a persuasive means which push the people into action. The study has five objectives which guides it. The success of a PSA campaign is measured by its ability to increase public awareness, change attitudes and encourage individuals to take specific actions in support of the cause. There is a need to assess whether PSAs lead to sustained behaviour change and long-term social impact, here lies the thrust of the study. The survey method was adopted for the study and the questionnaire used as the major instrument. According to the National Bureau of statistics (NBS) in 2022 the population of Eket resident was 220,600.